2008
DOI: 10.1213/ane.0b013e318172b993
|View full text |Cite
|
Sign up to set email alerts
|

The Antinociceptive Effects of Anticonvulsants in a Mouse Visceral Pain Model

Abstract: These results indicate that oxcarbazepine, gabapentin, and topiramate are effective in the writhing model in mice, in a dose range, which is not related to motor impairment; topiramate is the most potent and the most tolerable drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 28 publications
4
28
1
Order By: Relevance
“…Both pregabaline and gabapentine are central analgesics [39]. Gabapentinoids inhibited visceral hypersensitivity in the experimental animals, as well as irritable bowel syndrome in humans [41]. Smalls doses of gabapentine administered with morphine inhibit i.p.…”
Section: Other Types Of Calcium Channel Blockers Used In the Treatmenmentioning
confidence: 99%
“…Both pregabaline and gabapentine are central analgesics [39]. Gabapentinoids inhibited visceral hypersensitivity in the experimental animals, as well as irritable bowel syndrome in humans [41]. Smalls doses of gabapentine administered with morphine inhibit i.p.…”
Section: Other Types Of Calcium Channel Blockers Used In the Treatmenmentioning
confidence: 99%
“…The writhing reflex is characterized by the presence of abdominal muscle contractions associated with inward outstretching of the hind limbs, a hind paw reflex, or whole body extension. 7,9,14,17,20 The number of writhing reflexes, a measure of visceral pain, were recorded for a 30-min period. 20 Drugs and experimental protocol…”
Section: Acetic Acid-induced Writhingmentioning
confidence: 99%
“…[4][5][6] Like most anticonvulsants, gabapentinoids have also been found to have an antinociceptive effect in visceral pain. 7 Previous reports have shown that pregabalin inhibits trinitrobenzene sulfonic acid-induced allodynia in rats, and gabapentin inhibits acetic acid-induced irritation in rats. 8,9 Both pregabalin and gabapentin are recognized to reduce pain behaviour in colorectal distension and stress-induced visceral pain in rats.…”
mentioning
confidence: 99%
See 2 more Smart Citations